Structure and mechanisms of social succession - V. G. Rubanov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the study is caused by the necessity to develop the principals of attitude to sociocultural heritage within society transformation. The aim of the study is to clear up the structure of social succession in its historical establishing; to consider dialectic of social inheritance methods. Methods applied: logical historical and system-pragmatic analyses. The results of the study: The author has revealed the structure of social succession and analyzed the role of previous experience in the structure of modern activity. The paper demonstrates the pointed specifics of its elements and introduces the concept "speed of social succession", as actor's ability to absorb social memory. The main criteria of social succession mechanisms were determined and new types of social succession mechanisms were introduced. The author characterized the social succession mechanisms in their historical-cultural formation; the special aspects of succession mechanisms in primitive and high level social condition were emphasized. The paper introduces the notions: "factors of social influence", "common channels of perception", "external influence factors", "matrix socioculturalform". Together with the existent "homo sapiens" concept the author offers to use "homo patrimoniens" concept - heritable person.